Pelaksanaan Student Centered Learning Berbasis Daring pada Pembelajaran Sosiologi Siswa Kelas X IPS SMA PGRI 4 Padang pada Masa Pandemi Covid-19 - Muhammad Hafiz Ardyanli; Yanti Sri Wahyuni; Hefni Hefni (Horizon, 2021)
The background of the problem in the study is as follows: On March 17, 2020, the principal and head of the Padang city education office and the head of the West Sumatra 1 regional education office branch held a meeting in which one of the results was the dismissal of all levels of education and the teaching and learning process was shifted from face to face to face-to-face. online learning. The approach in this study is a descriptive research type Descriptive research type is a method to understand the individual that is carried out in an integrative and comprehensive manner in order to obtain a deep understanding of the individual and the problems he faces with the aim of solving the problem and obtaining improvement. good self-esteem (Rahardjo et al., 2011). The informants of this study were the curriculum representatives and Mr. Sociology subject teacher for class X, namely those who taught in class X IPS 1, 2, SMA PGRI 4 Padang. The results of the study were carried out with Sociology Teachers, the online learning process lasted for 5 weeks at SMA PGRI 4 Padang. Therefore, for 5 weeks, he carried out student centered learning based on online learning. The researchers concluded that Student Centered Learning could be implemented but it was not effective by using WhatsApp groups only, teachers should also use other applications, such as Google Classroom, Zoom, Telegram, Email, Telegram, Web Links provided by the school. So that the learning process can take place better